FGF5 gene involvement on fibre length of South American camelids - Melo R., Carola (2023)
One of the genes involved in hair fibre and hair follicle growth is the fibroblast growth factor 5 (FGF5). Mutation of this gene has been associated with long-haired phenotypes in several animal species, including llamas and alpacas. Blood samples were taken from 16 alpacas (9 Huacaya and 7 Suri), 6 llamas (4 Q'aras and 2 Chak'us), one vicuña and one guanaco. The polymorphisms related to fibre growth were analysed from a whole-genome sequence. The c.499≥T mutation was found to be present in both Huacaya and Suri alpaca breeds encoding a shorty protein of 166 amino acids. A one nucleotide deletion, c.351delC and a 12-nucleotide insertion (c.348_349insGCCATATAACAT) were present only in Chak’u breed llamas. This insertion encodes for a short, 119 amino acid protein, that affects the FGF5 gene and that would cause the growth of long fibres. In the case of mutation of c.499C>T, which causes a premature stop codon at amino acid 168, it is involved in alpaca fleece length. If there is no change in gene FGF5, fibre growth is not stimulated and this is what happens in the vicuña, guanaco, and Q’ara llamas, which presents a complete length of the gene with 270 amino acids. This study indicates that if the FGF5 gene is functional, South American camelids will have a short fibre growth, but if there are mutations affecting the expression of the FGF5 gene, animals will have long fleeces, and this would occur in the case of Huacaya and Suri alpacas, and Ckak’u llamas.